Acyl coenzyme A: 6-aminopenicillanic acid acyltransferase from Penicillium chrysogenum and Aspergillus nidulans. - Whiteman, P; Abraham, E; Baldwin, J; Fleming, MD; Schofield, C; Sutherland, J; Willis, A (1990)
A study of the final stages of the biosynthesis of the penicillins in Penicillium chrysogenum has revealed two types of enzyme. One hydrolyses phenoxymethyl penicillin to 6-aminopenicillanic acid (6-APA). The other, also obtained from Aspergillus nidulans, transfers a phenylacetyl group from phenylacetyl CoA to 6-APA. The acyltransferase, purified to apparent homogeneity, had a molecular mass of 40 kDa. It also catalyses the conversion of isopenicillin N (IPN) to benzylpenicillin (Pen G) and hydrolyses IPN to 6-APA. In the presence of SDS it dissociates, with loss of activity, into fragments of ca 30 and 10.5 kDa, but activity is regained when these fragments recombine in the absence of SDS.